Kajian Sintaksis Terhadap Klausa Pada Teks Berita Di Detik.Com - Muhamad Ichsan Nurjam’an; Aulia Ashari; Desma Hendriani Lay; Dini Cahya Dzulhijjah (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study was conducted to examine in depth the syntactic structure, particularly clause forms, used in news texts on the Detik.com portal. The main focus of the study was directed at observing the function, category, and role of each syntactic element that constructs clauses as important elements in journalistic language. The approach applied was qualitative through descriptive methods because the data collected was in the form of language elements, not numbers or statistics. The data sources were taken from a number of news articles in the which were selected purposively so that they could represent the style of language used by the media. Data was collected through documentation and observation-recording techniques to record every clause found in the news text. The analysis stages included the process of identification, grouping, and presentation of clause forms based on syntactic theory. With these steps, the researcher was able to determine the clause patterns that appeared and understand the function of each element in sentence construction.